Bush at war - Woodward, Bob, 1943- (New York : Simon & Schuster, 2002)
[In this book, the author] tells the behind-the-scenes story of how President George W. Bush and his top national security advisers, after the initial shock of the September 11 attacks, led the nation to war. Extensive quotations from the secret deliberations of the National Security Council - and firsthand revelations of the private thoughts, concerns and fears of the president and his war cabinet - make [the book a] chronicle of a modern presidency in time of grave crisis. Based on interviews with more than a hundred sources and four hours of exclusive interviews with the president, [it] reveals Bush's sweeping, almost grandiose, vision for remaking the world. [It] includes a ... portrait of CIA director George Tenet, ready and eager for covert action against terrorists in Afghanistan and worldwide. It [also] follows a CIA paramilitary team leader on a covert mission inside Afghanistan to pay off assets and buy friends with millions in U.S. currency carried in giant suitcases.-Dust jacket.
The President of the United States George W. Bush -- The Principals -- Vice President of the United States Dick Cheney -- Secretary of State Colin L. Powell -- Secretary of Defense Donald H. Rumsfeld -- Assistant to the President for National Security Affairs Condoleezza Rice -- Director of the Central Intelligence Agency George J. Tenet -- Chairman of the Joint Chiefs of Staff General Richard B. Myers -- White House Chief of Staff Andrew H. Card Jr. -- The Deputies -- Chief of Staff to the Vice President I. Lewis "Scooter" Libby -- Deputy Secretary of STate Richard L. Armitage -- Deputy Secretary of Defense Paul D. Wolfowitz -- Deputy Assistant to the President for National Security Affairs Stephen J. Hadley -- Deputy Director of the Central Intelligence Agency John E. McLaughlin -- Vice Chairman of the Joint Chiefs of Staff General Peter Pace -- Other Key Advisers -- Commander in Chief, U.S. Central Command General Tommy Franks -- Attorney General of the United States John D. Ashcroft -- Director of the Federal Bureau of Investigation Robert S. Mueller III -- Counselor to the President Karen P. Hughes -- Senior Adviser to the President Karl Rove -- White House Press Secretary Ari Fleischer -- The Central Intelligence Agency -- Deputy Director for Operations James L. Pavitt -- Director of the Counterterrorism Center Cofer Black -- Chief of Counterterrorist Special Operations Hank -- Jawbreaker Team Leader Gary -- The Northern Alliance -- Lead Commander Mohammed Fahim -- Commander of Forces in Northern Afghanistan Abdurrashid Dostum.
Includes index.
Keywords: Bush, George W. -- 1946- -- Military leadership; War on Terrorism, 2001-2009.; September 11 Terrorist Attacks, 2001.; United States -- Military policy -- Decision making; National security -- United States -- Decision making; Bush, George W. -- 1946- -- Interviews; United States -- Officials and employees -- Interviews; Bush, George W. -- 1946- -- Entrevistas; Bush, George W. -- 1946-; Guerra contra el terrorismo, 2001-; Ataques terroristas del 11 de septiembre, 2001.; Seguridad nacional -- Estados Unidos -- Toma de decisiones; z; x; Bush, George W. -- Military leadership; War on terrorism, 2001.; September 11 Terrorist Attacks, 2001.; Bush, George W; Elfter September; Terrorismus; 2; 2; USA; Golfstaaten; Bush, George Walker -- (1946-....).; Terrorisme -- y; z -- y; 2; x -- 1990-....; x; Afghanistan -- 2